Sparking Religious Conversion through AI? - McQueen, Moira (Religions, 2022)
This paper will take the stance that cognitive enhancement promised by the use of AI could be a first step for some in bringing about moral enhancement. It will take a further step in questioning whether moral enhancement using AI could lead to moral and or religious conversion, i.e., a change in direction or behaviour reflecting changed thinking about moral or religious convictions and purpose in life. One challenge is that improved cognition leading to better moral thinking is not always sufficient to motivate a person towards the change in behaviour demanded. While some think moral bioenhancement should be imposed if necessary in urgent situations, most religions today see volition in conversion as essential. Moral and religious conversion should be voluntary and not imposed, and recent studies that show possible dangers of the use of AI here will be discussed along with a recommendation that there be regulatory requirements to counteract manipulation. It is, however, recognized that a change in moral thinking is usually a necessary step in the process of conversion and this paper concludes that voluntary, safe use of AI to help bring that about would be ethically acceptable.